The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1161/hypertensionaha.106.080242
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces Angiogenesis in the Hypoxic Adult Mouse Heart In Vitro Through an AT 2 –B2 Receptor Pathway

Abstract: Abstract-Angiotensin II is a vasoactive peptide that may affect vascularization of the ischemic heart via angiogenesis. In this study we aimed at studying the mechanisms underlying the angiogenic effects of angiotensin II under hypoxia in the mouse heart in vitro. Endothelial sprout formation from pieces of mouse hearts was assessed under normoxia (21% O 2 ) and hypoxia (1% O 2 ) during a 7-day period of in vitro culture. Only under hypoxia did angiotensin II dose-dependently induce endothelial sprout formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 49 publications
1
28
3
Order By: Relevance
“…This study confirms previous observations [15][16][17] that Ang II in small amounts induces capillary tube formation from vascular endothelial cells. In keeping with previous observations, we show that the proangiogenic effects of Ang II are mediated by AT1R activation.…”
Section: Discussionsupporting
confidence: 93%
“…This study confirms previous observations [15][16][17] that Ang II in small amounts induces capillary tube formation from vascular endothelial cells. In keeping with previous observations, we show that the proangiogenic effects of Ang II are mediated by AT1R activation.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that angiotensin II, through its effect on angiotensin type 2 receptor, and bradykinin level, via bradykinin type 2 receptor, may affect the microvascular structure and function. 1,30 In our study, there was a significant increase in plasma renin activity in whites only, whereas the increase in capillary density occurred in all 3 of the ethnic groups. It is not known how far the responses of the renin-angiotensin system contributed to the changes in capillary density.…”
Section: He Et Al Effect Of Salt Reduction On Capillary Rarefactioncontrasting
confidence: 39%
“…In some studies a partial blockade was obtained with the AT 2 antagonist PD 123319 when a partial inhibition was also seen with A-779 and the B 2 receptor antagonist Hoe 140. Likewise, some BK effects are attenuated by PD 123319 (Bergaya et al 2004) and some AT 2 -mediated effects are attenuated by B 2 receptor blockade (Munk et al 2007). These observations illustrate the intricate relationship between Ang and kinin receptors, suggesting intracellular interactions via common signaling pathways or heterodimerization.…”
Section: Metabolic Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 99%